Kepraktisan Buku Ilmiah Populer Botani Tumbuhan Rawa Dalam Melatihkan Keterampilan Berpikir Kritis Mahasiswa - Dharmono Dharmono; Nurul Hidayati Utami; Mella Mutika Sari (Wahana-Bio: Jurnal Biologi dan Pembelajarannya, 2022)
Researches on the development of teaching materials in universities in the learning process to Improving higher-order thinking in plant Botany courses based on local materials are currently very necessary. Various forms of teaching materials were developed to Improving critical thinking skills. One of them is a popular scientific book.  This study aims to test the practicality of the popular scientific book (BIP) Botany of Swamp Plants in improving students' critical thinking skills in studying Higher Plant Botany. The type of research was Research and Development (R&D). The research subjects were 13 students of the Biology Education Study Program at Lambung Mangkurat University, with the object of research being BIP Botany of Swamp Plants. Practicality data was obtained based on the readability tests of three students, and 10 students. The research data were analyzed descriptively. The results showed that the BIP Botany of Swamp Plants which was developed practically (very practical category) was used to improve students' critical thinking skills.